The Effect Of Discounts And Word Of Mouth Communication On Purchasing Decisions At Src Al-Badar Wholesale Stores - Permana, Romi; Nugraha, Muhammad Rivaldhie Juniar; Amrullah, Amir Arkhan; Misbak, Misbak; Dedu, May (International Journal of Social Service and Research, 2024)
Currently, the business world is very competitive, especially in Indonesia. This is shown by the increasing number of traditional businesses that are starting to transition to modern businesses, or perhaps new modern businesses. This study uses Quantitative Research, a research method that collects data in the form of numbers or numerical data to be analyzed statistically. The results of hypothesis testing show that the variable Price Discount, Word of Mouth simultaneously has a positive effect on consumer purchase decisions. From the partial results, the discount has a positive and significant effect on the purchase decision at the Al-Badr src graosir store. Simultaneously, discounts and word of mouth communication have a positive and significant effect on product purchase decisions at the Al-Badr src wholesale store.